P122 Admission bicarbonate as a determinant of long-term mortality in obesity-related respiratory failure requiring acute non-invasive ventilation. (11th November 2022) - Krishnan, A; Antoine-Pitterson, P; Oakes, A; Gallagher, E; Cartwright, A; Mukherjee, R
Abstract : Introduction: Determinants of long-term mortality have been identified to a limited extent for hypercapnic patients with obesity-related respiratory failure (ORRF). It is known that a higher level of admission bicarbonate signifies more severe respiratory insufficiency, requiring higher non-invasive ventilation (NIV) pressures and longer duration of acute NIV in COPD patients. 1 This retrospective survey set out to identify whether admission bicarbonate is a predictor of 1-year mortality for ORRF requiring acute NIV. Methods: Arterial blood gas (ABG) measurements on admission and following initiation of acute NIV were extracted for the period April 2019 to March 2020 from our NIV quality database. Electronic patient records were searched for mortality. Log-rank test was used to correlate pre-NIV bicarbonate with 1-year mortality. Results: Forty-four ORRF patients required acute NIV (n = 44) in the period April 2019 to March 2020. Pre-NIV bicarbonate ranged from 14 to 35.5 mmol/L. Analysis identified that admission bicarbonate <23 mmol/L multiplied 1-year mortality by 8-fold (Hazard Ratio 8.44, p<0.0001) compared to values ≥23 mmol/L. Over 57% of patients with admission bicarbonate <23 mmol/L were dead (due to any cause) at 1 year, compared to 27% for bicarbonate ≥23 mmol/L. The pCO2 was not a significant predictor of long-term mortality. Discussion: Admission bicarbonate appears to be a significant predictor of all-cause mortality for hypercapnic ORRF requiring acute NIV, with levels <23 mmol/L octupling the mortality risk at 1 year. This cohort of ORRF patients with a low initial bicarbonate level on ABG seems to be those with multi-organ insufficiency due to obese morbidity, especially concurrent renal impairment. This is our first survey to quantify additional risk in the ORRF group. Further studies are needed on the effect of home mechanical ventilation on the prognosis of people with ORRF, especially those presenting with multi-organ insufficiency. References: Thomas A, et al. P267 Association of the length of non-invasive ventilation (NIV) with arterial bicarbonate level in COPD patients with acute hypercapnic respiratory failure (AHRF). Thorax 2011;66: A176-A177.